IMPACT: Prevalence and Predictors of High-Intensity End-of-Life Care Among Adolescents and Young Adults with Cancer in Ontario - Coltin, Hallie (Université d'Ottawa / University of Ottawa, 2021)
Adolescents and young adults (AYA) with cancer may experience disproportionate rates of high-intensity (HI) end-of-life (EOL) care. We conducted a population-based linkage study examining a decedent cohort of all Ontario AYA aged 15-21 years diagnosed with six primary cancers between 1992-2012. The primary composite outcome (HI-EOL care) included any of: intravenous chemotherapy ≤14 days from death; >1 emergency department visit; >1 hospitalization; or any intensive care unit (ICU) admission ≤30 days from death. Secondary outcomes included hospital deaths and measures of most invasive (MI)-EOL care. The outcome prevalence trends were examined, as were the predictors using regression models. Of 483 patients, 292 (60.5%) experienced HI-EOL care. AYA with hematological malignancies and relapsed disease experienced the highest and lowest odds of all outcomes, respectively. The prevalence of MI-EOL care may be increasing, especially for pediatric patients. This work is the first to identify LOC-based disparities in AYA EOL care.
Keywords: Cancer; End-of-life; Adolescent; Young adult